2019
DOI: 10.1021/acsami.9b07668
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Oxygen Reduction Reaction Activity and CO2 Tolerance of Cathode for Low-Temperature Solid Oxide Fuel Cells by in Situ Formation of Carbonates

Abstract: Development of low-cost and cobalt-free efficient cathode materials for oxygen reduction reaction (ORR) remains one of the paramount motivations for material researchers at a low temperature (<650 °C). In particular, iron-based perovskite oxides show promise as electrocatalysts for ORR because Fe metal is cheaper and naturally abundant, exhibit matched thermal expansion with contacting components such as electrolytes, and show high tolerance in a CO 2 -containing atmosphere. Herein, we demonstrated a new mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 67 publications
1
32
1
Order By: Relevance
“…The lattice parameter reduction originates from the incorporation of the smaller Li + into the Sr 2 + host. [30] This is confirmed by iodometric titration ( Table 1) which shows that the averaged iron valence in the oxides decreases with increasing Li concentration.…”
Section: Crystal Structures and Compositionsmentioning
confidence: 61%
See 4 more Smart Citations
“…The lattice parameter reduction originates from the incorporation of the smaller Li + into the Sr 2 + host. [30] This is confirmed by iodometric titration ( Table 1) which shows that the averaged iron valence in the oxides decreases with increasing Li concentration.…”
Section: Crystal Structures and Compositionsmentioning
confidence: 61%
“…[13][14][15] Ferrite-based perovskites, especially the cubic-structured SrFeO 3-δ (SF)-based perovskites, are promising cobalt-free cathode materials. [30] In particular, we found that the size mismatch of Li + (0.92 Å) dopant with the Sr 2 + (1.64 Å) host could also render a significant amount of Li + migrating to the surface and creating A-site deficiency in the bulk at high temperature. [16][17][18][19] The cubic SF structure can be stabilized with rare earth metals such as Bi 3 + , Sm 3 + , La 3 + at the A-site (Sr-site) and transition metals such as Ti 3 + , Mn 3 + , Ta 5 + , Nb 5 + , Hf 4 + , W 5 + , etc.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations